Chiral Switch in Antidepressants: A New Frontier for Safer and More Effective Personalized Therapies: A Review - Lavanya, Nandula; Gopalakrishna, Rashmi Nelligare (International Journal of Pharmaceutical Investigation, 2026)
Advancements in drug development emphasize enhancing efficacy, reducing side effects, and tailoring treatments to individual patient needs. Conventional antidepressant therapies often face limitations such as delayed onset of action, suboptimal efficacy, and undesirable side effects, leading to poor adherence and treatment resistance. These challenges underscore the need for more effective, safer, and patient-centered therapeutic approaches. Advancements in drug development now emphasize enhancing efficacy, minimizing side effects, and tailoring treatments to individual patient needs. This review explores the critical roles of chirality, single-enantiomer formulations, and personalized medicine in improving antidepressant therapy outcomes. A comprehensive literature analysis was conducted to assess how chirality affects drug-receptor interactions and pharmacokinetics. The review examined clinical data on single-enantiomer antidepressants, such as escitalopram, and evaluated personalized medicine strategies, including pharmacogenetic testing. Single-enantiomer formulations demonstrated superior efficacy and safety compared to their racemic counterparts. Isolating the active enantiomer improved receptor specificity, reduced off-target effects, and enhanced pharmacokinetic properties, including Absorption, Distribution, Metabolism, and Excretion (ADME). Personalized medicine approaches, particularly pharmacogenetic testing, enabled identification of genetic polymorphisms affecting drug metabolism and receptor sensitivity, thereby facilitating more precise and effective prescribing. Integrating chirality-based drug design with personalized medicine significantly advances antidepressant therapy. Single-enantiomer formulations and individualized treatment strategies offer improved therapeutic outcomes, reduced side effects, and greater predictability in clinical practice. Continued research and clinical adoption of these approaches hold promise for more effective and patient-centered management of depression.
Keywords: Chirality; Antidepressants; Single-Enantiomer; Therapeutic Effectiveness; Safety; Spectroscopic Drug Quality Control; Pharmacological Profiling; Personalized Medicine in Psychopharmacology